The Influence of Ease of Use, Application Features, and E-Trust on E-Satisfaction (Study on Motion Trade Investment Application Users) - Fitri Auliya Rijali; R. Yuniardi Rusdianto (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study is motivated by the growing development of financial technology, particularly in the category of online investment. One of the online investment apps available in Indonesia is Motion Trade. The objective of this study is to analyze the influence of ease of use, application features, and e-trust on e-satisfaction in the Motion Trade investment application, both simultaneously and partially. This research employs a quantitative methodological approach, with data obtained through the administration of an online questionnaire. A purposive sampling method, a type of non-probability sampling, was employed to acquire a sample of 156 respondents. For data analysis, this research employs the technique of multiple linear regression. The results reveal that the variables of ease of use, application features, and e-trust contribute positively and significantly to e-satisfaction, both simultaneously and individually. These findings suggest that improving ease of use, enhancing application features, and building user trust can effectively increase user satisfaction with the Motion Trade application.